Identifying Glass Compositions in Fly Ash - Aughenbaugh, Katherine L.; Stutzman, Paul; Juenger, Maria C. G. (Frontiers in Materials, 2016)
In this study, four Class F fly ashes were studied with a scanning electron microscope; the glassy phases were identified and their compositions quantified using point compositional analysis with k-means clustering and multispectral image analysis. The results showed that while the bulk oxide contents of the fly ashes were different, the four fly ashes had somewhat similar glassy phase compositions. Aluminosilicate glasses (AS), calcium aluminosilicate glasses (CAS), a mixed glass, and, in one case, a high iron glass were identified in the fly ashes. Quartz and iron crystalline phases were identified in each fly ash as well. The compositions of the three main glasses identified, AS, CAS, and mixed glass, were relatively similar in each ash. The amounts of each glass were varied by fly ash, with the highest calcium fly ash containing the most of calcium-containing glass. Some of the glasses were identified as intermixed in individual particles, particularly the calcium-containing glasses. Finally, the smallest particles in the fly ashes, with the most surface area available to react in alkaline solution, such as when mixed with portland cement or in alkali-activated fly ash, were not different in composition than the large particles, with each of the glasses represented. The method used in the study may be applied to a fly ash of interest for use as a cementing material in order to understand its potential for reactivity.